Erratum: Search for photons with energies above 1018 eV using the hybrid detector of the Pierre Auger Observatory - Aab, A. (2020)
1 Exposure calculation Due to a mistake in the numerical integration following eq. (6.2) of the original article [1], the exposure shown in figure 5 of the original article was incorrect. The correct exposure is shown in figure 1. 2 Upper limits on the integral photon flux and fraction The incorrect exposure affects the calculation of the upper limits on the integral photon flux following eq. (6.1) of the original article. The correct values for the upper limits are 0.038, 0.010, 0.009, 0.008 and 0.007 km−2 sr−1 yr−1 for threshold energies of 1, 2, 3, 5 and 10 EeV. The correct values for the upper limits on the integral photon fraction subsequently derived are 0.14 %, 0.17 %, 0.42 %, 0.86 % and 2.9 % for the same threshold energies. 3 Author list The author list of this erratum also corrects a mistake made in the original article, where F. Zuccarello was missing and Z. Zong was listed twice.